2021
DOI: 10.3390/genes12121905
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Genome-Wide Association Study for Indoleamine 2,3-Dioxygenase Activity Associated with Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) causes progressive damage to kidney function with increased inflammation. This process contributes to complex amino acid changes. Indoleamine 2,3-dioxygenase (IDO) has been proposed as a new biomarker of CKD in previous studies. In our research, we performed a metabolite genome-wide association study (mGWAS) to identify common and rare variants associated with IDO activity in a Korean population. In addition, single-nucleotide polymorphisms (SNPs) selected through mGWAS were furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…A genome-wide association study revealed a potential genetic connection between IDO activity and CKD, and Zhang et al discovered elevated IDO activity in individuals with type 2 diabetic nephropathy. 38 , 39 Antagonizing IDO was effective in reducing renal fibrosis during CKD, possibly due to the TGF-β-mediated tubular epithelial-mesenchymal transition. 40 , 41 The metabolism of tryptophan by IDO also has a direct or indirect link to atherogenesis, and Walker et al discovered that inhibiting IDO activity could potentially decrease thrombosis in CKD.…”
Section: Discussionmentioning
confidence: 94%
“…A genome-wide association study revealed a potential genetic connection between IDO activity and CKD, and Zhang et al discovered elevated IDO activity in individuals with type 2 diabetic nephropathy. 38 , 39 Antagonizing IDO was effective in reducing renal fibrosis during CKD, possibly due to the TGF-β-mediated tubular epithelial-mesenchymal transition. 40 , 41 The metabolism of tryptophan by IDO also has a direct or indirect link to atherogenesis, and Walker et al discovered that inhibiting IDO activity could potentially decrease thrombosis in CKD.…”
Section: Discussionmentioning
confidence: 94%
“…Various populations, including Koreans [28], have provided evidence to support the connection between IDO activity and CKD [7,13,14]. We have recently conducted an integrated metabolome and genome association analysis to identify genetic markers for detecting CKD in its early stages [15]. However, the previous study that focused on IDO activity had a limitation, as the correlation with CKD was moderately low.…”
Section: Discussionmentioning
confidence: 99%
“…IDO was also associated with diabetic nephropathy [12] and renal fibrosis [11]. Furthermore, several studies have demonstrated the association between CKD and IDO activity [7,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2022 ), psoriasis ( Vecellio et al. , 2021 ), and chronic kidney disease (CKD) ( Kim et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%